Uncertainty in humanities network visualization - Conroy, Melanie; Gillmann, Christina; Harvey, Francis; Mchedlidze, Tamara; Fabrikant, Sara Irina; Windhager, Florian; Scheuermann, Gerik; Tangherlini, Timothy R.; Warren, Christopher N.; Weingart, Scott B.; Rehbein, Malte; Börner, Katy; et al. (Frontiers in Communication, 2024)
Network visualization is one of the most widely used tools in digital humanities research. Networks have been used to study the structure of social groups, the circulation of texts, the relation of words within a text to one another, and countless other structures that are employed in digital humanities research. The idea of uncertain or "fuzzy" data is also a core notion in digital humanities research. Yet network visualizations in digital humanities do not always prominently represent uncertainty. In this article, we review some of the principles for visualizing uncertainty of different kinds and consider how these visualizations could be used in digital humanities research. We focus on elements that can be integrated into the network diagram, rather than the displayed data, or accompanying diagrams. We show that, rather than being unique to the digital humanities, uncertainty in this realm is in many ways analogous to the concept and uses of uncertainty in other disciplines; we also show how techniques for visualizing uncertainty in fields like climate science and bioinformatics could be used to represent more prominently some of the types of uncertainty that we find in humanities data.